# Thread: Integration of Rational Expression - Alternative Method

1. ## Integration of Rational Expression - Alternative Method

Hello everyone,

I integrated the following rational expression correctly, but one of my steps differ from that one of the book. Could anyone tell me if what I did is still correct?

Thank you!

---

1. Integrate: $\displaystyle \int \frac{\sqrt{x - 4} + x}{x - 4} dx$

---
$\displaystyle \int \frac{\sqrt{x - 4} + x}{x - 4} dx$

= $\displaystyle \int (x - 4)^{-1/2} dx + \int \frac{x}{x - 4}dx$

Let $\displaystyle u = x - 4$ and $\displaystyle du = dx$. Therefore, $\displaystyle x = u + 4$.

= $\displaystyle \int u^{-1/2} du + \int \frac{u + 4}{u}du$

= $\displaystyle 2\sqrt{x - 4} + \int \frac{u}{u} du + \int \frac{4}{u} du$

= $\displaystyle 2\sqrt{x - 4} + x + \ln(x - 4)^4 + C$

---

However, my practice workbook integrated $\displaystyle \int \frac{u}{u} du$ as $\displaystyle u$, and then substituted $\displaystyle x - 4$ back into the equation.

So according to the workbook, its last step would be:

= $\displaystyle 2\sqrt{x - 4} + u + \ln(x - 4)^4 + C$

= $\displaystyle 2\sqrt{x - 4} + (x - 4) + \ln(x - 4)^4 + C$

= $\displaystyle 2\sqrt{x - 4} + x + \ln(x - 4)^4 + C$

2. I think the way you did it kind of implies that $\displaystyle \int \frac{u}{u}du=x$ because of the way you kept your terms in order. The book's method is more correct in my opinion as it notes that the above integral doesn't equal x, but u + C, then back-substitutes x-4 for u and combines all the constants into one C.

3. Hello, scherz0!

What you did is correct.
. . I would not have simplifed first as you did . . .

We are given: .$\displaystyle \int \frac{\sqrt{x - 4} + x}{x - 4}\,dx$

Let: $\displaystyle \sqrt{x-4} \:=\: u \quad\Rightarrow\quad x-4\:=\:u^2 \quad\Rightarrow\quad x \:=\: u^2+4 \quad\Rightarrow\quad dx \:=\:2u\,du$

Substitute: .$\displaystyle \int \frac{u + (u^2+4)}{u^2}\,(2u\,du) \;\;=\;\;2\int\frac{u^2+u-4}{u}\,du \;\;=\;\; 2\int\left(u + 1 - \frac{4}{u}\right)\,du$

. . . . . . $\displaystyle = \;\;2\left(\frac{u^2}{2} + u - 4\ln|u|\right) + C \;\;=\;\;u^2 + 2u - 8 \ln|u| + C$

Back-substitute: .$\displaystyle (x - 4) + 2\sqrt{x-4} - 8\ln\left(\sqrt{x-4}\right) + C$

. . . . . . . . . . .$\displaystyle =\;\;x - 4 + 2\sqrt{x-4} - 8\ln(x-4)^{\frac{1}{2}} + C$

. . . . . . . . . . .$\displaystyle = \;\;x + 2\sqrt{x-4} - 4\ln(x-4) + \underbrace{C - 4}_{\text{a constant}}$

. . . . . . . . . . .$\displaystyle = \;\;x + 2\sqrt{x-4} - 4\ln(x-4) + C$